2006
DOI: 10.1385/jmn:30:1:145
|View full text |Cite
|
Sign up to set email alerts
|

Bioscavenger for Protection From Toxicity of Organophosphorus Compounds

Abstract: Current antidotal regimens for organophosphorus compound (OP) poisoning consist of a combination of pretreatment with a spontaneously reactivating AChE inhibitor such as pyridostigmine bromide, and postexposure therapy with anticholinergic drugs such as atropine sulfate and oximes such as 2-PAM chloride (Gray, 1984). Although these antidotal regimens are effective in preventing lethality of animals from OP poisoning, they do not prevent postexposure incapacitation, convulsions, performance deficits, or, in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 3 publications
1
65
0
Order By: Relevance
“…In humans, immune responses to mutated hBChE are likely to be weaker or absent, because the modified amino acids are confined to the interior of the catalytic gorge (Pancook et al, 2003), poorly available to immune surveillance. It should also be emphasized that extensive research in animals as well as human subjects has revealed no toxicity from hBChE protein (Clark et al, 2005;Saxena et al, 2006). Therefore, the principal concern in hBChE-based gene therapy must be the direct effects of the vector per se along with immune responses to the viral protein or novel DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, immune responses to mutated hBChE are likely to be weaker or absent, because the modified amino acids are confined to the interior of the catalytic gorge (Pancook et al, 2003), poorly available to immune surveillance. It should also be emphasized that extensive research in animals as well as human subjects has revealed no toxicity from hBChE protein (Clark et al, 2005;Saxena et al, 2006). Therefore, the principal concern in hBChE-based gene therapy must be the direct effects of the vector per se along with immune responses to the viral protein or novel DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Large quantities of native BChE are well tolerated by all tested species (Lynch et al, 1997;Carmona et al, 2000;Doctor and Saxena, 2005). Mice with high circulating levels of human BChE showed no clinical signs, postmortem examinations revealed no abnormalities in serum chemistry or hematology (Saxena et al, 2006), and the acoustic startle reflex remained normal (Clark et al, 2005). Finally, daily administration of the partially purified wild-type protein for several weeks to human subjects has evoked no adverse b and c).…”
Section: Use Of Human Bchementioning
confidence: 99%
“…Genetic aspects (see above) or intoxication with some compounds such as organophosphate pesticides and/or organophosphonate nerve agents (see below) are sources of false positive findings. BuChE is capable of detoxifying a large number of exogenous substances: procaine 13 , succinylcholine 14 , cocaine 15 , heroin, acetylsalicylic acid 16 , and it can also protect the body from the impact of organophosphorus AChE inhibitors 17 . However the primary reason for the existence of BuChE is still unknown.…”
Section: Butyrylcholinesterasementioning
confidence: 99%